A Distributed Algorithm to Schedule TSCH Links under the SINR Interference Model - Silva, José Carlos Da; Assis, Flávio (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2017)
Industrial environments are typically characterised by high levels of interference. Therefore, standards for industrial wireless sensor networks (WirelessHART, ISA 100.11a, and IEEE 802.15.4e) have defined a time division and multichannel-based mode of operation, in which time slots and channel pairs are assigned to links representing communication between nodes. In IEEE 802.15.4e this mode of operation is called Timed Slotted Channel Hopping (TSCH). In this paper we describe a distributed algorithm to define such an assignment for a given wireless network. In particular, the algorithm is efficient, scalable and was developed for the Signal-to-Interference-plus-Noise-Ratio (SINR) model, currently considered the most appropriate to develop and analyse algorithms for wireless networks when interference is taken into consideration. Previous approaches to this problem are mainly centralised, based on a simple (or none) interference model or do not consider multiple physical channels. The described algorithm applies also to the Internet of Things, characterised by high scale and presence of interference.